Man, technology and cosmos: on the significance of Friedrich Dessauer’s book "Man and Cosmos. The Dispute about Technology" in translation by A.Yu. Nesterov. Review of the book "Man and Cosmos. Experience. Dispute about Technology" translated by A.Yu. Nesterov - Anastasia A. Lisenkova; Grigory L. Tulchinsky (Семиотические исследования)
The paper reviews Dessauer’s key ideas related to the philosophy of technology, the interaction between humans and technology, and the concept of the "fourth realm" of technology, which is interpreted as a new form of being created by humankind. The authors of the review emphasize the relevance of Dessauer’s ideas in the context of modern technological challenges, such as the development of artificial intelligence technologies, biotechnology, virtual and augmented reality, and others. Special attention is paid to the role of technology as a creative and destructive force, as well as its influence on the transformation of human perception of reality and human relations with the cosmos. Special attention should be paid to the contribution of the translator A.Yu. Nesterov, who not only preserved the stylistic and terminological features of the original, but also made the text accessible to the Russian-speaking audience by providing it with explanatory comments. Dessauer’s book is presented as a key text in the philosophy of technology, which continues to be relevant in the era of contemporary technological development, which is changing both our lives and our understanding of ourselves. The review raises questions about the limits of human control over technology, the ethical implications of its development, and the possibilities of applying the concept of the metacosmos to the analysis of contemporary technological progress.